Studies of stress and strain state of compound plates by the numero-analytical method of potentials - Бродовий, В. Л. (Proceedings of National Aviation University (archive), 2000)
Theory issues and techniques of applying the numero-analytical method of potential to analysis of compound Kirchoff-Love plates are under consideration. A linear approximation of densities is applied, a new method of transforming angular members id used, a multidimensional generalization of interpolation by boundary element group diameters is applied to iterate the solution. Examples are given, classes of problems efficiency solvable by the technique suggested are outlined